1993
DOI: 10.1111/j.1574-6968.1993.tb05867.x
|View full text |Cite
|
Sign up to set email alerts
|

The slime of coagulase-negative staphylococci: Biochemistry and relation to adherence

Abstract: In recent years, infections of implanted plastic devices by coagulase‐negative staphylococci have become a major cause of septicaemia in human patients. The causal bacterial species is usually Staphylococcus epidermidis and these organisms grow as a biofilm adherent to a solid surface. Several methods have been introduced to assess the mass of adherent bacteria and the slimy matrix in which they are embedded. Some methods measure total biofilm, others measure the organisms or the slime alone. In vitro, the typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(22 citation statements)
references
References 85 publications
0
22
0
Order By: Relevance
“…The chemical composition of the staphylococcal biofilms has been intensively investigated. Several authors consider PIA (Mack et al, 1996a), teichoic acid (Hussain et al, 1993) or proteins (Hussain et al, 1997) to be main components required for staphylococcal biofilm formation. It is assumed that staphylococcal strains isolated from infected sites -and particularly from prosthetic devices -should be able to form a biofilm (Bf+), produce PIA (PIA+), and possess the icaADBC operon (ica+).…”
Section: Discussionmentioning
confidence: 99%
“…The chemical composition of the staphylococcal biofilms has been intensively investigated. Several authors consider PIA (Mack et al, 1996a), teichoic acid (Hussain et al, 1993) or proteins (Hussain et al, 1997) to be main components required for staphylococcal biofilm formation. It is assumed that staphylococcal strains isolated from infected sites -and particularly from prosthetic devices -should be able to form a biofilm (Bf+), produce PIA (PIA+), and possess the icaADBC operon (ica+).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of some gram-positive bacteria, such as the staphylococci, the chemical composition of EPS may be quite different and may be primarily cationic. Hussain et al (40) found that the slime of coagulase-negative bacteria consists of a teichoic acid mixed with small quantities of proteins.…”
Section: Biofilm Structurementioning
confidence: 99%
“…Early studies described the solid component of the glycocalyx as primarily composed of teichoic acids (80%) and staphylococcal and host proteins (Hussain et al, 1993). Host-derived proteins, such as fibrin, may be derived from the conversion of fibrinogen by the staphylococcal coagulase -prothrombin complex (Akiyama et al, 1997).…”
Section: Staphylococcus Biofilmsmentioning
confidence: 99%